MEDAN MAKNA KERAJINAN TANGAN YANG TERBUAT DARI ANYAMAN PADA MASYARAKAT MELAYU SAMBAS - Mulyani, Wike; Partiantoro, Partiantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research focus on observations on cultural objects, namely handicrafts made of wicker in Sambas Malay society. The problem in this research is how component of meaning, kind of meaning and meaning, and semantic function. The purpose of this study is to describe the components of meaning, type of meaning and meaning, and semantic function. This research uses qualitative research method. Researchers analyzed the data collected by analyzing the components of meaning. In addition, researchers also conducted an analysis of the type of meaning and meaning based on the analysis of handicrafts woven in lexical and colocation. The study also features an analysis of semantic functions. The overall data obtained from the interview and recording process conducted by researchers during research in Sambas district. The entire data is based on the meaning component with the classification, ie the material, the usefulness of the equipment, the type of activity, the duration of use, the handle, and the frame on the equipment. Meaning and meaning of classification of lexical meanings and colloquial meanings, as well as semantic functions of storing, wrapping, marking, base, filtering, gameplay, head protection, confinement, cleansing, barrier, food cover.Keywords: Handicraft, meaning field, Sambas Malay